Oratorium A and other 4th century christian buildings in Salona - Kaić, Iva (Array, 2013)
The Episcopal complex in Salona consists of basilicae geminatae, baptistery, two oratorium buildings (Oratorium A and Oratorium B), bishop’s palace and related economic facilities. From the mid-19th century up to the mid-20th century distinguished scholars, F. Carrara, F. Bulić, W. Gerber and E. Dyggve, conducted archaeological excavations of Episcopal complex. During these excavations considerable attention has been given to the Oratorium A which is situated in the north-western corner of the Episcopal complex, near the city walls. Scholars interpreted the Oratorium A as a private house with thermae and concluded that the object was adapted for the Christian cult in the Pre-Constantinian period. During the 2nd half of the 20th century B. Gabričević and N. Cambi studied the functional and spatial organization of the Oratorium A. They accepted the thesis of Oratorium A as the oldest Christian cult edifice in Salona. However, revisionary archaeological excavations of Oratorium A, conducted by a Croatian-French team, started in 2000 and lasted until 2007. Results so far have shown that Oratorium A should be included in the sacral objects of the Constantinian period in Dalmatia. This would make the Oratorium A, along with the cathedral built at the time of bishop Primus (died cca. in 325) in the area of the Episcopal complex, the only preserved Constantinian church in Salona.